Seasonal effect on biomarker responses in sentinel species: innovation in mangrove conservation status assessment - Souza, Caroline Araújo de [UNESP]; Duarte, Luis Felipe de Almeida [UNESP]; Zanotto, Flávia Pinheiro [UNESP]; Ortega, Priscila; Moreira, Renata Guimarães; Pinheiro, Marcelo Antonio Amaro [UNESP] (Springer Nature, 2022)
We evaluated the environmental quality in mangrove areas of the Western Atlantic with different levels and history of contamination, considering biomarkers for the crab Ucides cordatus. For this purpose, specimens were collected in two climatic seasons (rainy and dry seasons) and assays of genotoxicity (MN, micronucleus), cytotoxicity (NRRT, neutral red retention time) and biochemical (MT, metallothionein; and LPO, lipoperoxidation) were conducted. In the most impacted mangroves, there was an increase in the mean of micronucleus (frequency of MN/1000), which was associated with a shorter retention time (minutes of NRRT). In contrast, the most pristine areas showed MN < 3 and NRRT < 100 min, with no seasonal effect, indicating a lower effect of degenerative processes by xenobiotics. The rainy season was more harmful, especially regarding cytogenotoxicity. The use of bioindicator species for environmental monitoring should be guided by an analysis of biomarkers considering the season, because during the period of highest rainfall, biomarkers values can change.
Keywords: Bioindicator; Lipoperoxidation; Metallothionein; Micronucleus; Neutral red; Seasonality